P169 Long-term safety of pirfenidone in patients with idiopathic pulmonary fibrosis: pooled analysis of 4 clinical trials. (15th November 2016) - Noble, PW; Albera, C; Lancaster, L; Hormel, P; Hulter, H; Costabel, U
Abstract : Introduction: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive and irreversible disease that requires long-term management. The objective of this study was to assess the long-term safety of pirfenidone from a pooled analysis of 4 clinical studies. Methods: All patients who received pirfenidone (2403 mg/d) in the Phase 3 studies (ASCEND/CAPACITY) and/or the long-term extension study (RECAP) were included in this analysis. Safety outcomes were assessed during the period from the first dose until 28 days after the last dose of pirfenidone in either study. Analyses included the final data from the Phase 3 studies and RECAP (data cut, June 30, 2015). Results: The pooled population included 1216 patients with a cumulative total exposure of 3366 patient-exposure years. Median pirfenidone exposure was 25.9 months (range, 0–105 months), with a mean dose of 2306 mg/d. 99% of patients reported ≥1 treatment-emergent adverse event (TEAE). 57% of patients reported a serious TEAE (0.51 per patient-exposure year [PPEY]), the most common being IPF (21.5%) and pneumonia (9.3%; Table ). TEAEs led to discontinuation in 45% of patients (0.17 PPEY), the most common being IPF (15.9%), rash (1.6%) and nausea (1.6%). Median survival on treatment (or ≤28 days after discontinuation of pirfenidone) was 82.6 months. Conclusions: The safety findings from this pooled analysis are consistent with the known safety profile of pirfenidone and the underlying disease of IPF.